2020
DOI: 10.1016/j.iotech.2020.02.001
|View full text |Cite
|
Sign up to set email alerts
|

High multiplex analysis of the immune microenvironment in bone marrow trephine samples using GeoMX™ digital spatial profiling

Abstract: Background: To date, studies into the bone marrow (BM) immune microenvironment have been limited due to reliance on the analysis of BM aspirates in which the microenvironmental context is lost. GeoMX™ digital spatial profiling (DSP) is a new technique developed for the analysis of formalin-fixed paraffin-embedded tissue samples which allows high multiplex analysis of protein expression in multiple user-defined regions within a tissue section. We examined the applicability of this technique to the analysis of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…The gut microenvironment and inflammatory changes of the immune system are closely related . The expression of LYZ, which was implicated with Paneth cells, directly affected the gut microorganisms, , and the immune response associated with the gut microenvironment could significantly affect the dynamics of bone metabolism. In this study, the ovariectomized rats after being treated by ACP and E2 with normalized bone mass acquired an altered gut microbiota and maintained the number of Paneth cells compared to OVX, revealing that osteoporosis drugs may alter the intestinal bacteria of ovariectomized rats by influencing the expression of Paneth cells. The Paneth cell-derived antimicrobial peptides, including LYZ, plays an important role in the regulation of gut microbiota.…”
Section: Discussionmentioning
confidence: 68%
“…The gut microenvironment and inflammatory changes of the immune system are closely related . The expression of LYZ, which was implicated with Paneth cells, directly affected the gut microorganisms, , and the immune response associated with the gut microenvironment could significantly affect the dynamics of bone metabolism. In this study, the ovariectomized rats after being treated by ACP and E2 with normalized bone mass acquired an altered gut microbiota and maintained the number of Paneth cells compared to OVX, revealing that osteoporosis drugs may alter the intestinal bacteria of ovariectomized rats by influencing the expression of Paneth cells. The Paneth cell-derived antimicrobial peptides, including LYZ, plays an important role in the regulation of gut microbiota.…”
Section: Discussionmentioning
confidence: 68%
“…Thus, it seems that DSP has the potential to be an accurate and reproducible tool for determining patient prognosis following checkpoint inhibition. The usefulness of DSP is not just limited to fresh-frozen or FFPE tissue samples; indeed, one study showed how DSP could be extended to bone marrow trephine samples with unprecedented high-plex spatial profiling of the bone marrow microenvironment [ 96 ]. This finding means that DSP might serve to identify biomarkers and potential drug targets specific to haematological malignancies.…”
Section: Digital Spatial Profilingmentioning
confidence: 99%
“…While this is particularly useful in interrogating the TME and features of interest, it prevents whole-tissue analysis especially in larger excisional biopsy samples and may lead to a biased hypothesis-driven sample analysis [ 88 , 97 ]. In addition, DSP has poor single-cell resolution, requiring at least 10 cells in an ROI to generate adequate counts [ 96 , 98 ]. This restriction might limit the effectiveness of DSP when analysing tumour regions with low cellularity.…”
Section: Digital Spatial Profilingmentioning
confidence: 99%
“…Larger longitudinal-assessment studies comparing those with persisting PGF vs those with resolution are required. Utilization of other novel techniques such as digital spatial profiling applied to bone marrow trephines 73 and gene-expression profiling will give further insight to the immunobiology of PGF.…”
Section: Immune Dysfunction (Climate)mentioning
confidence: 99%